Methodical Approach to the Selection of a Rational Variant of the Allocation of Financial Resources for the Foreign Patenting of the Results of Intellectual Activity - Aleksandr Gennad’evich Podol’Skii; Valerii Viktorovich Trushchenkov (Учёт. Анализ. Аудит)
Subject. The subject of the research in this article are the results of intellectual activity, obtained during the implementation of research and development work under the state defense order. Purpose. The purpose of the research is to ensure the effective use of financial resources for the legal protection of the results of intellectual activity created within the framework of the state defense order abroad, in the interests of protection against unauthorized copying of domestic military products, increasing its competitiveness and export volumes. Methodology. The article uses the existing methodology for estimating the cost of licenses based on royalties, for the base of which the cost of a single sample of military products is accepted. Results. Within the framework of the article, an approach to choosing a rational variant of the allocation of financial resources for foreign patenting of the results of intellectual activity is proposed, which ensures the maximum revenue from the sale of licenses for granting the right to use the results of intellectual activity owned by the state and the production of weapons samples. Conclusions. The developed methodical approach has a practical focus, it also is consistent with domestic and international legislation in the field of intellectual property protection, it takes into consideration the organizational and economic aspects of the disposition of intellectual property rights created under the state defense order. The methodological provisions formulated in the article are aimed at increasing the level of legal protection of the results of intellectual activity contained in exported military products, intensifying innovation activity in the Russian Federation and increasing the flow of funds to the federal budget from the disposal of intellectual property owned by the state.